2004
DOI: 10.1515/jpem.2004.17.4.645
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Testicular Adrenal Rest Tumours in Adolescent and Adult Males with Congenital Adrenal Hyperplasia: Basal and Follow-up Investigation After 2.6 Years

Abstract: Aim:To study the course of asymptomatic testicular adrenal rest tumours in patients with congenital adrenal hyperplasia (CAH) and the association between tumour changes and glucocorticoid therapy adjustments. Patients and Methods: Fifteen male patients with CAH (21-hydroxylase deficiency), in whom asymptomatic testicular adrenal rest tumours had been found at a baseline investigation, underwent scrotal ultrasonography and venous blood sampling (for LH, FSH and testosterone) on average 2.6 years later. The leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 20 publications
0
46
0
6
Order By: Relevance
“…ACTH may be an important stimulator of tumour growth, because ACTH receptors are present on the tumour tissue, and some authors describe a relationship between poor hormonal control and progression of tumour growth (22,23). Although adequacy of substitution therapy was not systematically assessed in our patients, none of our patients had documented periods of poor hormonal control in early childhood or puberty.…”
Section: Discussionmentioning
confidence: 89%
“…ACTH may be an important stimulator of tumour growth, because ACTH receptors are present on the tumour tissue, and some authors describe a relationship between poor hormonal control and progression of tumour growth (22,23). Although adequacy of substitution therapy was not systematically assessed in our patients, none of our patients had documented periods of poor hormonal control in early childhood or puberty.…”
Section: Discussionmentioning
confidence: 89%
“…However, if high gonadotropin levels are found, they can be indicative of a testicular failure (22,30). Whereas some investigators found that TARTs regressed and spermatogenesis was reactivated when glucocorticoid therapy was instituted or intensified (11,31), others report that patients remain azoospermic (27,32). The use of dexamethasone (0.25-0.5 mg p.o.…”
Section: Hormonal Treatment and Outcomementioning
confidence: 99%
“…However, intensifying of glucocorticoid treatment with suppression of ACTH secretion is not always successful in reducing tumor size and even in well-controlled CAH patients, with normal or suppressed plasma ACTH levels, testicular adrenal rest tumors are found (2,3,12). Therefore, most probably other unknown factors contribute to tumor growth.…”
mentioning
confidence: 99%